Effective Opportunity Discovery Using Out-of-Band Sensing in Cognitive Radio Networks: Seamless Communication and Throughput - Yalew Zelalem Jembre (The Graduate School, Ajou University, 2012)
In cognitive radio networks (CRN), proactive spectrum sensing, i.e. sensing Out-of-Band channels that are not currently in use or is not considered for several network setups. Cognitive radio (CR) users, so called secondary users (SUs), should avoid interference with primary users (PUs), which are the owner of the licensed band, while trying to access the unused licensed or unlicensed band, for spectrum utilization, by using In-Band (IB) sensing. When PUs request to access their band, SUs need to vacate the band, thus it is inconvenient to provide seamless communication. In this paper, we suggest Out-of-Band (OB) sensing to guarantee seamless communication, by minimizing the time required to discover a new unused spectrum in order to continue communication. Since proactive type of sensing has impact on the throughput if it is used with inappropriate scheme, we provide a mathematical analysis to demonstrate that the effect our proposed scheme on the, achievable and aggregate, throughput due to OB sensing is insignificant.
학위논문(석사)아주대학교 일반대학원 :컴퓨터공학과,2012. 2